MORPHOSTRATIGRAPHY OF FERRUGINOUS DURICRUSTS IN THE NORTHWEST OF PARANÁ - Fumiya, Marcel Hideyuki; Cordeiro Santos, Leonardo José; Riffel, Silvana Bressan (Revista Brasileira de Geomorfologia, 2019)
Soils constitute an important mean for studying the conditioning processes of the evolution of the relief, considering that in them materials related to events modeling the relief can be preserved. In the Northwest region of Paraná, a manifestation of ferruginous duricrust related to relief sculpture is observed, but there are no detailed studies on these deposits. In this sense, this work aims to analyze these ferruginous materials present in the study area, through the morphological description of profiles with duricrusts, as well as to study these materials by X-ray diffraction and micromorphology, seeking to understand the current organization of ferruginous materials on top of hillocks and hills. Therefore, a mapping of relief features supported by ferruginous duricrusts, previously identified by Fumiya et al., (2016) was used. A morphological description of profiles with ferruginous duricrust in 14 relief features showed that 11 features present truncations between horizons and colluvial layers, indicating that probably the duricrusts are rudaceous paleopavement, that were covered by colluvium.